Effectiveness of ultrasound (US) and slightly acidic electrolyzed water (SAEW) treatments for removing Listeria monocytogenes biofilms - Hongrui Ren; Yu Quan; Shaokang Liu; Jianxiong Hao (Ultrasonics Sonochemistry)
Biofilms can persist in food industry environments leading to repeated cross-contamination, thus threatening human health. Slightly acid electrolyzed water (SAEW) and ultrasound have emerged as environmentally-friendly antimicrobial agents. However, their bactericidal efficacy is not high when used alone. In the present study, the effect of ultrasound combined with SAEW on removing Listeria monocytogenes biofilms from a glass surface was evaluated. Listeria monocytogenes biofilms were treated by immersion in sterilized deionized water (control treatment), immersion in sterilized deionized water combined with ultrasound (US treatment), immersion in SAEW (SAEW treatment), immersion in SAEW combined with ultrasound treatment (SAEW + US treatment), immersion in SAEW followed by immersion in sterilized deionized water combined with ultrasound (SAEW − US treatment), and immersion in sterilized deionized water combined with ultrasound followed by immersion in SAEW (US − SAEW treatment). The results showed that treating biofilms by US − SAEW treatment led to the lowest number of Listeria monocytogenes, the lowest amount of biofilm remaining on the glass slide were visualized by crystal violet staining and scanning electron microscope, and a minimal content of extracellular polymeric substances. Overall, the highest biofilm removal efficacy was observed for the US − SAEW treatment.